Studi Eksperimen Unjuk-Kerja Modulasi DBPSK pada Platform Software-Defined Radio (SDR) - Marpanaji, Eko; Trilaksono, Bambang Riyanto; Langi, Armein ZR; Kurniawan, Adit (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
This paper addresses Differential Binary Phase Shift Keying (DBPSK) modulation implemented on SDR platform for the development of digital data communications based on SDR. DBPSK modulation performance perceived at Packet Error Rate (PER) is evaluated in terms of Eb/No or S/N ratio, carrier frequency, bit rate, gain, roll-off factor of root Nyquist filter or root raised cosine filter, and of size of payload from delivered data. Based on this results, the smallest PER could be obtained by setting Eb/No value which is greater than 13 dB, carrier frequency of at least 0,3 MHz, optimum bit rate of 256 kbps, optimum range payload size of 2000 up to 4000 bytes, and roll-off factor of Nyquist or root-raised cosine filter of 0.1<alfa<0.9.